The role of the teacher as a subject of pedagogical culture (Pedagogy of Higher and Secondary Education, 2009)
The article it devoted to the research of the importance of creative legacy of modern teacher m the leaching process.
Keywords: culture; pedagogical culture; professional culture; system of skills